Implementation of islamic inheritance law in Makassar City (Study on Class IA Makassar Religious Court) - Mustaring,; Muh. Sudirman,; Bakhtiar, (Technium Social Sciences Journal, 2023)
The purpose of this study is to find out 1) How is the inheritance distribution system in the Muslim community in the city of Makassar, 2) What factors influence the implementation of Islamic inheritance law in the city of Makassar. The research is a research (Field Research), the location of research of the Makassar Religious Court class IA, with a normative sociological approach. In this study, several data collection techniques were used, namely; interviews, observations and documentation. The results showed that; 1) The implementation of inheritance law among the Muslim community of Makassar City varies greatly, some distribute and hand over property to each of their children in the form of grants strengthened by a statement letter, some go through deliberation or compromise for the sake of creating peace and benefit in their family environment, some settle their inheritance with an Islamic inheritance law approach, and some through the help of religious courts, Both through mediation and through court decisions, and of course there are also in their own way regardless of the rights of other heirs. 2) The implementation of Islamic inheritance law in Makassar City has not been fully implemented, this is influenced by factors, namely; the substance of the law, the level of knowledge of the community, the level of knowledge of the apparatus, the level of public perception, the level of customs (legal culture) of the community and the level of legal awareness of the community.